Some New Inequalities of Jordan Type for Sine. (31st October 2013) - Zeng, Shan-Peng; Wu, Yue-Sheng
Abstract : The authors find some new inequalities of Jordan type for the sine function. These newly established inequalities are of new form and are applied to deduce some known results.